Evaluation the effect of the masticatory and perioral muscles on the growth of the maxilla after cleft palate repair (Latakia University Journal -Medical Sciences Series, 2021)
The aim of this study is to evaluate the effect of the orbicularis oris and masseter muscles on maxillary growth in surgically treated cleft palate patients and the possibility of guiding maxillary growth towards a more balanced form. This study included 20 patients of both sexes with hard or soft palate clefts or with oro-nasla fistula within the study’s age group. Those patients were divided into two groups: a control group of 10 patients were treated surgically using the two flap (bardach) technique and a test group treated with the same surgical technique with botulinum toxin injection in the aforementioned muscles.An impression was taken and a cast was prepared before surgical treatment and 6 month after surgery. Intercanine distance and Intermolar distance was measured in both casts and the difference was compared between the study and control groups. The difference in both Intercanine and Intermolar distance was greater in the study compared with the control group and it was statistically significant. As a result we can deduce that injecting botulinum toxin lead to an increase in the Intercanine and Intermolar distance and an increase in maxillary width. Injecting botulinum toxin in the orbicularis oris and masseter muscles was found to be safe in children within the conditions of this study and lead to an increase in transvers maxillary growth which is needed in surgically treated cleft palate patients because of the growth impairment caused be the following scat tissue formation.